Transgenerational effects of paternal heroin addiction on anxiety and aggression behavior in male offspring. Issue 1 (December 2016) - Farah Naquiah, Mohd; James, Richard; Suratman, Suraya; Lee, Lian; Mohd Hafidz, Mohd; Salleh, Mohd; Teh, Lay
Abstract Background Heroin addiction is a growing concern, affecting the socioeconomic development of many countries. Little is known about transgenerational effects on phenotype changes due to heroin addiction. This study aims to investigate changes in level of anxiety and aggression up to four different generations of adult male rats due to paternal exposure to heroin. Methods Male Sprague–Dawley rats were exposed with heroin intraperitoneally (i.p.) twice-daily for 14 days with increasing dosage regimen (F0-heroin). Male Sprague–Dawley rats (6-weeks-old) were divided into: (1) heroin exposed group (F0-heroin) and (2) control group treated with saline solution (F0-control). The dosage regime started with the lowest dose of 3 mg/kg per day of heroin followed by 1.5 mg/kg increments per day to a final dose of 13.5 mg/kg per day. Offspring were weaned on postnatal day 21. The adult male offspring from each generation were then mated with female-naïve rats after 2 weeks of heroin absence. Open field test and elevated plus maze test were used to study the anxiety level, whereas resident intruder test was used to evaluate aggression level in the addicted male rats and their offspring. Results Heroin exposure in male rats had resulted in smaller sizes of the litters compared to the control. We observed a higher anxiety level in the F1 and F2 progenies sired by the heroin exposed rats (F0) as compared to the control rats. Paternal heroin exposure also caused significantly more aggressive offspring in F1 compared to the control. The same pattern was also observed in the F2. Conclusion Our results demonstrated that the progenies of F1 and F2 sustained higher levels of anxiety and aggression which are due to paternal heroin exposure.